A portable device for detecting prothrombin time
By using aggregation-induced luminescence carbon dots in the prothrombin time detection device, the problem of unsatisfactory detection accuracy and stability in the existing technology is solved, and prothrombin time detection with high accuracy and stability is achieved.
Patent Information
- Application Number
- CN202410377766.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-03-29
AI Technical Summary
The existing prothrombin time detection devices rely on electrochemical detection methods, resulting in poor detection accuracy and stability.
Aggregation-induced luminescence carbon dots (AIE-CDs) are used as detection materials, and the extrinsic coagulation pathway is activated through the reaction between plasma and tissue factor, and the changes in the fluorescence signal of the carbon dots are used to detect prothrombin time.
The accuracy and stability of prothrombin time detection are achieved, and reliable detection results are obtained through the single excitation and dual emission characteristics and viscosity response characteristics of carbon dots.
Smart Images

Figure CN118376609B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical detection, and in particular to a portable device for detecting prothrombin time. Background Art
[0002] For people with cerebral embolism, myocardial infarction, and thromboembolism, coagulation disorders or postoperative complications require long-term use of anticoagulants. In terms of the anticoagulant effect and price of anticoagulants on the market, warfarin is a more commonly used anticoagulant. While taking warfarin, it is necessary to regularly monitor the prothrombin time or international normalized ratio (PT / INR) to determine the coagulation function, and then use the drug rationally to avoid adverse drug reactions.
[0003] Existing PT / INR tests are generally carried out in laboratories, which is not conducive to portable home testing for patients who require long-term anticoagulation treatment. Based on this, a small coagulation detector that can detect PT / INR at home has been developed. Chinese patents CN110057890A and CN108614017A have developed electrochemical sensors for portable PT / INR detection. However, the lack of stability in electrochemistry leads to reduced accuracy of the test results. In the journal literature, Nicholas et al. reported a handheld impedance coagulation detector that prints electrodes on the surface of a flexible substrate to convert the chemical signals of coagulation into electrical signals. When using this method for detection, the size of the electrical impedance and the test frequency will lead to deviations in the test results, and the detection stability is poor. It is urgent to develop a prothrombin time detection device that is easy to operate and has high accuracy to meet application requirements. Summary of the invention
[0004] The present invention is intended to provide a portable device for detecting prothrombin time, so as to solve the technical problem that the detection accuracy and stability of the prothrombin time detection device in the prior art are not ideal due to reliance on electrochemical detection.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] A portable device for prothrombin time detection comprises a detection area fixed with aggregation-induced luminescence carbon dots, wherein the detection area is used to receive plasma; the aggregation-induced luminescence carbon dots are synthesized by the following method: dithiosalicylic acid or citric acid is mixed with triethylenetetramine or tetraethylenepentamine, and the mixture is reacted at 160-220°C for 6-12h to obtain the obtained mixture.
[0007] Furthermore, it also includes a separation zone for separating whole blood to obtain plasma; a transition zone is connected between the separation zone and the detection zone.
[0008] Furthermore, the materials of the separation zone, detection zone and transition zone are all glass fiber membrane or asymmetric polysulfone membrane; the separation zone is 1-3 cm long, 0.5-1 cm wide, 0.5-0.9 mm thick, and has a porosity of 35%-55%; the detection zone has a diameter of 0.6-1.2 cm, a thickness of 0.2-0.4 mm, and a porosity of 35%-55%; the transition zone is 0.2-0.4 cm long, 0.2-0.4 cm wide, 0.2-0.4 mm thick, and has a porosity of 35%-55%.
[0009] Furthermore, the separation zone, the detection zone and the transition zone constitute an intermediate layer; the intermediate layer is arranged in an outer shell formed by the top layer and the bottom layer; the outer shell is made of modified plastic or polyvinyl chloride, with a length of 8-10 cm and a width of 1.5-3 cm; the top layer is provided with a sample addition area with a diameter of 0.3-0.5 cm and a signal observation area with a diameter of 0.8-1.4 cm.
[0010] Furthermore, it also includes a tissue factor mixture for dripping on the detection area receiving plasma; it also includes a dark box, which is used to provide 340-380nm excitation light to the detection area receiving plasma after the tissue factor mixture is dripped, and is also used to detect the wavelength of the fluorescence emission peak of the detection area until the wavelength of the fluorescence emission peak stabilizes to a constant value.
[0011] Further, the prothrombin time is obtained according to the following method: PT = [(T end -T start ) / 2]×0.2942+8.147; where PT is prothrombin time, T start T is the time of adding tissue factor mixture, end It is the time for the wavelength of the fluorescence emission peak in the detection zone to stabilize to a constant value.
[0012] The technical solution also provides a method for synthesizing aggregation-induced luminescent carbon dots, which comprises first dissolving dithiosalicylic acid or citric acid in an acetic acid solution, then adding triethylenetetramine or tetraethylenepentamine, and stirring for 6-15 minutes; maintaining the mixture at a temperature of 160-220°C for 6-12 hours, and obtaining aggregation-induced luminescent carbon dots after the reaction.
[0013] The technical solution also provides a method for synthesizing aggregation-induced luminescence carbon dots to obtain aggregation-induced luminescence carbon dots.
[0014] The technical solution also provides the application of aggregation-induced luminescence carbon dots in the preparation of a prothrombin time detection device. The prothrombin time detection device is used to contact plasma with aggregation-induced luminescence carbon dots, detect the red shift of the emission peak wavelength of the aggregation-induced luminescence carbon dots under excitation, and record the time when the red shift phenomenon occurs.
[0015] The technical solution also provides an application of a portable device for detecting prothrombin time in the preparation of equipment for detecting coagulation function.
[0016] In summary, the principles and beneficial effects of the present invention are:
[0017] The carbon dots synthesized by this technical solution have good biocompatibility and viscosity response characteristics, and can be dissolved in various organic and non-organic solvents. In solvents with low viscosity such as water and PBS, the ligands on the surface of the carbon dots can rotate freely and emit blue / green fluorescence; when the solvent is a solvent with a higher viscosity value such as glycerol and ethylene glycol, the high viscosity of the solvent restricts the internal rotation state of the ligands on the surface of the carbon dots. The carbon dots have a red shift in their excitation wavelength due to the restricted internal rotation of the molecules, and emit yellow / red fluorescence.
[0018] The plasma sample initiates the exogenous coagulation pathway under the action of the coagulation reagent, causing the fluorescence intensity of the AIE-CDs to change. Under the action of continuous excitation light, the aggregation-induced luminescence carbon dots generate a fluorescence-time curve. The curve includes the following characteristic points: the moment the coagulation reagent is added, the time corresponding to the fluorescence intensity starting to change T start ; After a period of time, the fluorescence value tends to stabilize. end , according to the preset formula and characteristic points, calculate the PT value (prothrombin time), the preset formula is: PT = [(T end -T start ) / 2]×0.2942+8.147, where 0.2942 and 8.147 are correction coefficients.
[0019] This technical solution is the first to apply aggregated luminescent carbon dots to a prothrombin time detection device. In order to achieve an ideal detection effect and ensure the accuracy, stability and parallelism of the detection results, it is necessary to control the following technical links: the concentration of the carbon dot solution in the fixed detection area, the fixed time, the method of attaching and fixing the carbon dots to the detection area, the thickness of the detection area, etc. The above technical key points are the first exploration and research findings of the inventors, which are very critical to the realization of new uses of aggregated luminescent carbon dots. Otherwise, even if the carbon dots have the emission peak red shift phenomenon at different viscosities, and the plasma will produce coagulation under the action of tissue factor, it is difficult to achieve accurate detection of prothrombin time through the carbon dots of this solution.
[0020] The beneficial effects of this technical solution are summarized as follows:
[0021] (1) Synthesize a new type of aggregation-induced luminescent carbon quantum dots, which have the following advantages: single excitation dual emission characteristics; as the viscosity of the solution environment increases, its emission peak will show a significant red shift.
[0022] (2) Using tissue factor to react with plasma, the exogenous coagulation pathway is initiated, converting soluble fibrinogen into insoluble fibrin. Carbon quantum dots have the property of aggregation-induced luminescence, which converts the coagulation process into a fluorescent signal, and this property is used for portable detection of prothrombin time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : The emission spectra of the carbon dots in Example 1 in aqueous solutions of different concentrations.
[0024] Figure 2 ] is the fluorescence intensity of the carbon dots of Example 1 at emission wavelengths of 437 nm and 625 nm in aqueous solutions of different concentrations.
[0025] Figure 3 The fluorescence change percentages of the carbon dots of different concentrations in Example 1 in the dispersed state and the aggregated state (mean ± standard deviation, n = 3).
[0026] Figure 4 This is an exploded view of the test card of Example 2.
[0027] Figure 5 This is a three-dimensional diagram of the test card of Example 2 (after assembly).
[0028] Figure 6 This is a microscopic picture of the detection area of Example 2 before and after capturing red blood cells.
[0029] Figure 7 The curve showing typical voltage value changes over time in Example 3 is shown in FIG.
[0030] Figure 8 The statistical graph of coagulation time at different ratios of whole blood and tissue factor in Example 3 (mean ± standard deviation, n = 3, **** indicates p < 0.0001).
[0031] Fig. 9 The fluorescence intensity deviation values of different carbon dot fixation methods in Comparative Example 1 (mean ± standard deviation, n = 3, ** indicates p < 0.01). DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following examples and experimental examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial sources.
[0033] The specific reference numerals are as follows: top layer 1, bottom layer 2, sample addition area 3, signal observation area 4, separation area 5, detection area 6.
[0034] Example 1: Synthesis of aggregation-induced emission carbon dots
[0035] Add 10-15 parts by mass of dithiosalicylic acid or citric acid to 1-3 parts by volume of an acid solution and stir until completely dissolved (for example: 10-15 mg: 1-3 mL). The acid solution can be an acetic acid solution with a volume fraction of 80%-90%. Then, add (2-5)×10-4 parts by volume of triethylenetetramine or tetraethylenepentamine to the mixed solution and stir for 6-15 minutes. Subsequently, the mixed solution is transferred to a polytetrafluoroethylene reactor and maintained at 160°C-220°C for 6-12 hours. After the reaction solution is naturally cooled, it is filtered and dried. Finally, the acetic acid and water are removed by rotary evaporation to obtain powdered carbon dots.
[0036] The carbon dots prepared by the above parameters all have a significant red shift phenomenon of emission peaks in different viscosity environments under excitation, that is, under ultraviolet excitation light of 340-380nm, in a low viscosity environment (for example, a water solution environment with a mass fraction of 0%-50% of glycerol or dimethyl silicone oil solute used to simulate the state before plasma coagulation), an emission peak appears at 420-460nm; in a high viscosity environment (for example, a water solution environment with a mass fraction of 70%-100% of glycerol or dimethyl silicone oil solute used to simulate the state after plasma coagulation), an emission peak appears at 610-650nm. The carbon dots of this scheme have good biocompatibility and viscosity response characteristics. In a solution with a low environmental viscosity, the ligands on the surface of the carbon dots can rotate freely and emit blue / green fluorescence; when the environmental viscosity is high, the carbon dots have their excitation wavelength red-shifted due to the restricted molecular internal rotation, emitting yellow / red fluorescence.
[0037] The subsequent experiments were carried out in the following specific manner to prepare carbon dots, which were used as examples to demonstrate their efficacy:
[0038] 12 parts by mass (e.g., 12 mg) of dithiosalicylic acid was added to 2 parts by volume (e.g., 2 mL) of 90% acetic acid solution and stirred until completely dissolved. Then, 2.25×10 -4 Volume (e.g. 2.25×10 -4 mL) of tetraethylene pentamine (TEP) was added and stirred for 12 min. Subsequently, the mixed solution was transferred to a polytetrafluoroethylene reactor and kept at 180 °C for 10 h. After the reaction solution was cooled naturally, it was filtered and dried. Finally, acetic acid and water were removed by rotary evaporation to obtain powdered carbon dots.
[0039] The obtained powdered carbon dots were dispersed in aqueous solutions of different concentrations at 2 mg / mL, and then the fluorescence intensity of the emitted light at different emission wavelengths was detected under the condition of 365 nm laser excitation. The aqueous solutions of different concentrations were prepared with glycerol as the solute. The experimental results are shown in Figure 1. From the experimental data, we can see that when the solute concentration of glycerol is low (0%-50%), the wavelength corresponding to the maximum emission peak of the carbon dots is 420-450nm (437nm); when the solute concentration of the aqueous solution is increased (70%-90%), the wavelength corresponding to the maximum emission peak of the carbon dots is 610-640nm (625nm). It can be seen that with the increase of the viscosity of the solution, the emission peak of the carbon dots will show an obvious red shift, with single excitation and double emission characteristics. At the same time, the fluorescence intensity at the emission wavelengths of 437nm and 625nm in aqueous solutions of different concentrations was detected, as shown in Figure 2. Figure 2 As shown: the emission peak around 625nm appears when the concentration of the plasma coagulation simulant in the aqueous solution is ≥70%, and the fluorescence intensity of the emission peak is already very obvious around 90%; the emission peak around 437nm appears when the concentration of the plasma coagulation simulant in the aqueous solution is ≤50% (≥0%). Therefore, detecting the fluorescence intensity of the carbon dots of this scheme at two emission wavelengths under different viscosity environments can reflect the environmental viscosity. For example, strong fluorescence appears around 625nm, but strong fluorescence does not appear around 437nm, indicating that the environmental viscosity is high; strong fluorescence does not appear around 625nm, but strong fluorescence appears around 437nm, indicating that the environmental viscosity is low.
[0040] The percentage change of fluorescence of carbon dots with different concentrations (0.5, 1, 2, 3, 4, 5, 6 mg / mL) in the dispersed state and the aggregated state. FL2 is the fluorescence intensity of carbon dots in the aggregated state, and FL1 is the fluorescence intensity of carbon dots in the dispersed state. 50% propylene glycol was used to simulate the aggregated state after plasma coagulation, while the dispersed state of carbon dots was simulated by directly dispersing carbon dots in water. The experimental results show that there is no significant difference in the percentage change of fluorescence of carbon dots with different concentrations in the dispersed state and the aggregated state. The experimental results can be found in Figure 3 .
[0041] Example 2: Prothrombin time detection device
[0042] Prothrombin time detection devices include Figure 4 and Figure 5 The detection card shown. The detection card includes a shell composed of a top layer 1 and a bottom layer 2, an intermediate layer is arranged between the top layer 1 and the bottom layer 2, the intermediate layer includes a separation area 5 and a detection area 6, and a transition zone is connected between the separation area 5 and the detection area 6. A sample adding area 3 and a signal observation area 4 are arranged on the top layer 1, the sample adding area 3 is located above the separation area 5, and is used to add the sample to the sample adding area 3; the signal observation area 4 is located above the detection area 6, and is used to observe the change of the fluorescence intensity of the carbon dots in the detection area 6.
[0043] The top layer 1 and the bottom layer 2 are buckled together, and the material is modified plastic or polyvinyl chloride. The detection card (the outer contour formed by the buckling of the top layer 1 and the bottom layer 2) is 8-10 cm long and 1.5-3 cm wide; the diameter of the sample adding area 3 is 0.3-0.5 cm, and the diameter of the signal observation area 4 is 0.8-1.4 cm. The separation area 5 is 1-3 cm long and 0.5-1 cm wide; the detection area 6 has a diameter of 0.6-1.2 cm; the transition zone between the separation area 5 and the detection area 6 is 0.2-0.4 cm long and 0.2-0.4 cm wide.
[0044] The material of the separation zone 5 is a glass fiber membrane or an asymmetric polysulfone membrane (the glass fiber membrane is used as an example in subsequent specific experimental studies), which is cut according to the size requirements of the above-mentioned separation zone 5, and the thickness of the separation zone 5 is 0.5-0.9mm. The material of the detection zone 6 is a glass fiber membrane or an asymmetric polysulfone membrane (the glass fiber membrane is used as an example in subsequent specific experimental studies), which is cut according to the size requirements of the above-mentioned detection zone 6, and the thickness of the detection zone 6 is 0.2-0.4mm. The detection zone 6 needs to be coated with carbon dots before subsequent assembly. The material of the transition zone between the separation zone 5 and the detection zone 6 is a glass fiber membrane, which is cut into a specified size with a thickness of 0.2-0.4mm. The porosity of the separation zone 5, the detection zone 6, and the transition zone materials is 35%-55%. Paste the cut separation area 5, detection area 6, and transition zone on the PVC base plate in sequence, cut the PVC base plate into a suitable size for assembly, for example: a rectangular test strip with a length of 3-5 cm and a width of 0.5-1 cm, and then install it in the detection card shell made of modified plastic or polyvinyl chloride (between the top layer 1 and the bottom layer 2).
[0045] Among them, the specific operation method of fixing the carbon dot solution to the detection area 6 is as follows: the carbon dots are configured into a solution with a concentration of 2-4 mg / mL, mixed and set aside; after the detection area 6 is cut, it is placed in the above solution, placed on a shaker (100-300 rpm / min) at room temperature for 5-10 minutes, taken out, and dried at 37°C for 2-4 hours.
[0046] As an example, the subsequent experimental study uses a test card with the following parameters (the parameters of separation zone 5, detection zone 6 and transition zone mainly affect the test effect):
[0047] The separation zone 5 is 1 cm long, 1 cm wide, 0.8 mm thick, and has a porosity of 47%; the detection zone 6 is 0.7 cm in diameter, 0.35 mm thick, and has a porosity of 41%; the transition zone between the separation zone 5 and the detection zone 6 is 0.3 cm long, 0.2 cm wide, 0.35 mm thick, and has a porosity of 41%. The carbon dots are configured into a solution with a concentration of 2 mg / mL, mixed, and set aside; after the detection zone 6 is cut, it is placed in the above solution, placed on a shaker (100 rpm / min) at room temperature for 10 minutes, taken out, and dried at 37°C for 2 hours. When adding the sample, add the sample at the end of the separation zone 5 away from the detection zone 6, and 100 μL of undiluted whole blood can be added to the separation zone 5. After 10-20 seconds, the plasma can be separated. Figure 6 (Top) shows a microscopic image of separation zone 5 when whole blood is not added to the device; Figure 6 (Middle) shows a microscopic image of separation zone 5 after whole blood is added to the device (the glass fiber membrane mesh structure intercepts red blood cells); Figure 6 (Below) is a photograph of the middle layer after adding whole blood to separate plasma. It can be seen that the red blood cells and plasma can be separated after the whole blood passes through the separation area 5. Most of the red blood cells are adsorbed in the separation area 5, and most of the plasma is adsorbed to the detection area 6 through the transition zone.
[0048] The prothrombin time detection device also includes a dark box, which is a conventional device for observing fluorescence in the prior art, including a box body and a transparent observation window arranged on the top of the box body. A camera or a smart phone can be placed at the transparent observation window to record the fluorescence color development of the detection card in the box body. An ultraviolet light source and a filter are provided at the front end of the dark box. The filter can absorb light of other wavelengths and only allow ultraviolet light of a specific wavelength to pass through; the power switch is provided at the front end of the outer side of the dark box, and an external power supply system is required. The excitation wavelength range of the ultraviolet excitation light source is 340-380nm.
[0049] During the test, turn on the ultraviolet excitation light source in advance and adjust it to the test state; after adding whole blood to the separation area 5 on the test card, wait for 20-30 seconds, add a certain amount of tissue factor to the test area 6, and immediately put the test card into the dark box, and start to continuously read and analyze the data through the fluorescence analysis module.
[0050] After adding tissue factor, the time T start At this time, the wavelength position of the fluorescence emission peak is X. As the plasma viscosity gradually increases, the fluorescence emission wavelength gradually redshifts until the wavelength position of the fluorescence emission peak no longer changes (position Y). At this time, the timing T end , and then calculate by the preset formula (PT=[(T end -T start ) / 2]×0.2942+8.147), where 0.2942 and 8.147 are correction coefficients.
[0051] For a typical curve of the voltage value (the degree of fluorescence color change) over time for prothrombin time detection using the device of this scheme, see Figure 7 (TF: indicates that tissue factor is added to the detection area; PBS indicates that PBS is added to the detection area instead of tissue factor). The equipment used to detect fluorescence intensity can achieve continuous monitoring through the sampling period setting. For example, if the sampling period is set to 500ms, the detection is performed every 500ms, and each detection is counted as one time, which is the counts (number of times) on the horizontal axis in the figure. In order to facilitate the processing of the results, the digital quantity module of the fluorescence detector converts the fluorescence color (red shift of the emission peak) into a voltage value. The change in voltage value is the change in fluorescence color. C1 represents the moment when tissue factor is added (sampling period × counts corresponding to the horizontal axis), and C2 represents the moment when the emission peak is no longer red shifted, that is, the moment when the fluorescence color no longer changes (sampling period × counts corresponding to the horizontal axis).
[0052] Embodiment 3:
[0053] 100 μL of undiluted whole blood was added to the separation area of the test card prepared in Example 2 for detection, and the excitation light was 365 nm. The volume ratio of whole blood and tissue factor is shown in Tables 1 and Figure 8 . From the experimental data, it can be seen that the ratio of plasma and tissue factor needs to be maintained at ≥1:2, so that the detected coagulation time is relatively stable. Among them, the tissue factor is taken from the prothrombin time assay reagent (Thromborel S) in the prothrombin time assay kit (coagulation method), which can be purchased by commercial means. Among them, the reagent containing tissue factor used contains freeze-dried human placental thromboplastin (≤60g / L) and calcium chloride (about 1.5g / L).
[0054] Table 1: Whole blood and tissue factor ratio and coagulation time test results
[0055] Whole blood: tissue factor Coagulation time (seconds) 1:1 14.1 1:2 12.1 1:3 12.0 1:4 12.1
[0056] Comparative Example 1: Attempt of carbon dot fixation method
[0057] The carbon dot solution was fixed to the detection area by the dipping method (the method used in Example 2) and the coating method. After being treated by the two different methods, the paper base of the detection area was placed at 40°C for drying overnight, and the fluorescence distribution of the detection area treated by the two methods was observed under ultraviolet excitation. The fluorescence intensity of 5 positions was extracted, and the relative standard deviation of the fluorescence distribution intensity was calculated. The experimental results are shown in Fig. 9 Among them, the coating method is to directly add the carbon dot solution of the same concentration exceeding the maximum loading amount of the detection area to the center of the detection area through a sample gun, and obtain it after drying at 37°C.
[0058] Comparative Example 2: Attempt to synthesize raw materials of carbon dots
[0059] In the process of trying to synthesize carbon dots, a variety of materials were tried, as follows:
[0060] This comparative example is the same as Example 1, except that tetraethylenepentamine is replaced with an equal mass of melamine. According to the experimental method shown in Example 1, the synthesized carbon dots are tested, and it is found that with the change of environmental viscosity, the emission peak of the carbon dots does not show a red shift phenomenon, and only shows an emission peak at 420-450nm.
[0061] Comparative Example 3: Exploration of the concentration of carbon dot solution
[0062] This comparative example was carried out with reference to Example 2. The ratio of whole blood to tissue factor during detection was 1:3. However, different concentrations of carbon dot solutions were tried to prepare the detection device (the concentration of the carbon dot solution used to immerse the detection area). The parameter settings and experimental results are shown in Table 2. The whole blood samples were all taken from healthy individuals.
[0063] Table 2: Detection effect of different carbon dot solution concentrations
[0064]
[0065] It can be seen from the above data that when the aggregation-induced luminescence carbon dots of this scheme are used to prepare a portable device for prothrombin time detection, the concentration control of the carbon dots in the detection area immersed in the aggregation-induced luminescence carbon dots solution has a significant effect on the detection effect. When the concentration of the carbon dot solution is too high (≥5mg / mL), the test result will be greatly different from the true value (the prothrombin time measured by the fully automatic coagulation analyzer is regarded as the true value), and the coefficient of variation of the repeated test results is large, and the parallelism and stability of the test results are not ideal. Therefore, in order to ensure more accurate test results, it is advisable to use a carbon dot solution concentration of ≤4mg / mL. In addition, in actual operation, it is generally believed that the coefficient of variation should be as small as possible. If the coefficient of variation is ≥5%, it means that the stability and accuracy of the detection method are very unsatisfactory and should be abandoned.
[0066] Comparative Example 4: Exploration of the immersion time of the carbon dot solution in the detection area
[0067] This comparative example was carried out with reference to Example 2, and the ratio of whole blood to tissue factor was 1:3 during the detection, except that different carbon dot solution soaking time in the detection area was tried. The parameter settings and experimental results are shown in Table 3. Among them, the whole blood samples were all taken from healthy individuals.
[0068] Table 3: Detection effect of different carbon dot solutions on the immersion time of the detection area
[0069]
[0070] From the above data, it can be seen that when the aggregation-induced luminescence carbon dots of this scheme are used to prepare a portable device for prothrombin time detection, the time control of the detection area soaked in the aggregation-induced luminescence carbon dots solution has a significant effect on the fluorescence generation effect. If the soaking time is too long (≥13min), it will cause uneven fluorescence in the detection area, affecting the detection effect, and the deviation value can reach 6.04%. When the soaking time is reduced to 10min or less, the deviation value drops to less than 2%, among which soaking for 10min is the best.
[0071] Comparative Example 5: Exploration of the Thickness of the Detection Area
[0072] This comparative example was carried out with reference to Example 2, and the ratio of whole blood to tissue factor was 1:3 during the detection, except that different thicknesses of the detection area were tried. The parameter settings and experimental results are shown in Table 4. The whole blood samples were all taken from healthy individuals.
[0073] Table 4: Test results of different test area thicknesses
[0074]
[0075] It can be seen from the above data that when the aggregation-induced luminescence carbon dots of this scheme are used to prepare a portable device for prothrombin time detection, when different thicknesses of the detection zone substrate are used, the prothrombin time is significantly affected. When the thickness of the detection zone exceeds 0.75 mm, the test result will be greatly different from the true value (the prothrombin time measured by the fully automatic coagulation analyzer is regarded as the true value). Therefore, in order to ensure more accurate test results, the thickness of the detection zone substrate is preferably ≤0.61 mm. In addition, in actual operation, it is generally believed that the coefficient of variation should be as small as possible. If the coefficient of variation is ≥5%, it means that the stability and accuracy of the detection method are very unsatisfactory and should be abandoned. If the thickness of the detection zone is further reduced to 0.2-0.4 mm, the detection value of the prothrombin time is still consistent with the detection result of the traditional method, and the coefficient of variation is maintained at about 2%. However, if the thickness of the detection zone continues to decrease, it cannot effectively carry the sample plasma, so its thickness cannot be too low. Therefore, a detection zone thickness of 0.2-0.61 mm can meet the requirements of detection accuracy and stability. In order to save materials, the thickness of the detection zone is generally controlled at 0.4 mm or less.
[0076] The above are only examples, please provide according to the actual situation. As many comparative examples as possible can be provided to illustrate the non-obviousness of the technical solution through comparison. The above are only embodiments of the present invention, and the common sense such as the known specific technical solutions and / or characteristics in the solution are not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the scope of protection of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A portable device for detecting prothrombin time, characterized in that: The invention comprises a detection area fixed with aggregation-induced luminescence carbon dots, and the detection area is used for receiving plasma; the aggregation-induced luminescence carbon dots are synthesized by the following method: dithiosalicylic acid or citric acid is mixed with triethylenetetramine or tetraethylenepentamine, and reacted at 160-220°C for 6-12h to obtain the obtained mixture.
2. A portable device for prothrombin time detection according to claim 1, characterized in that: It also includes a separation zone for separating whole blood to obtain plasma; a transition zone is connected between the separation zone and the detection zone.
3. A portable device for prothrombin time detection according to claim 2, characterized in that: The materials of the separation zone, detection zone and transition zone are all glass fiber membrane or asymmetric polysulfone membrane; the separation zone is 1-3cm long, 0.5-1cm wide, 0.5-0.9mm thick, and has a porosity of 35%-55%; the detection zone has a diameter of 0.6-1.2cm, a thickness of 0.2-0.4mm, and a porosity of 35%-55%; the transition zone is 0.2-0.4cm long, 0.2-0.4cm wide, 0.2-0.4mm thick, and has a porosity of 35%-55%.
4. A portable device for prothrombin time detection according to claim 3, characterized in that: The separation zone, the detection zone and the transition zone constitute an intermediate layer; the intermediate layer is arranged in an outer shell formed by the top layer and the bottom layer; the outer shell is made of modified plastic or polyvinyl chloride, with a length of 8-10 cm and a width of 1.5-3 cm; a sample addition area with a diameter of 0.3-0.5 cm and a signal observation area with a diameter of 0.8-1.4 cm are arranged on the top layer.
5. A portable device for prothrombin time detection according to claim 4, characterized in that: It also includes a tissue factor mixture for dripping on the detection area receiving plasma; it also includes a dark box, which is used to provide 340-380nm excitation light to the detection area receiving plasma after the tissue factor mixture is dripped, and is also used to detect the wavelength of the fluorescence emission peak of the detection area until the wavelength of the fluorescence emission peak stabilizes to a constant value.
6. A portable device for prothrombin time detection according to claim 5, characterized in that: The prothrombin time is obtained as follows: PT = [(T end -T start ) / 2]×0.2942+8.147; where PT is prothrombin time, T start T is the time of adding tissue factor mixture, end It is the time for the wavelength of the fluorescence emission peak in the detection zone to stabilize to a constant value.
7. Application of aggregation-induced emission carbon dots in the preparation of a prothrombin time detection device, characterized in that: The aggregation-induced luminescence carbon dots are synthesized by the following method: first dissolving dithiosalicylic acid or citric acid in an acetic acid solution, then adding triethylenetetramine or tetraethylenepentamine, stirring for 6-15 minutes; maintaining the temperature at 160-220° C. for 6-12 hours, and obtaining aggregation-induced luminescence carbon dots after the reaction; The prothrombin time detection device is used to contact plasma with aggregation-induced luminescence carbon dots, detect the red shift of the emission peak wavelength of the aggregation-induced luminescence carbon dots under excitation, and record the time when the red shift phenomenon occurs.
8. Use of a portable device for detecting prothrombin time according to any one of claims 1 to 5 in preparing equipment for detecting coagulation function.
Citation Information
Patent Citations
Prothrombin time examination method and device
CN108614017A
Blood coagulation detection chip and electrochemical sensor
CN110057890A
Peroxide fluorescence colorimetric dual-mode detection method based on carbon dot fluorescence inner filter effect
CN112964686A